Philosophy and religion in early medieval China - Chan, Alan Kam-leung; Lo, Yuet-keung (SUNY series in Chinese philosophy and culture, 2010)
Introduction / Alan K.L. Chan -- Sage nature and the logic of namelessness : reconstructing He Yan's explication of Dao / Alan K.L. Chan -- Tracing the Dao : Wang Bi's theory of names / Jude Soo-Meng Chua -- Hexagrams and politics : Wang Bi's political philosophy in the Zhouyi zhu / Tze-Ki Hon -- Li in Wang Bi and Guo Xiang : coherence in the dark / Brook Ziporyn -- The sage without emotion : music, mind, and politics in Xi Kang / Ulrike Middendorf -- The ideas of illness, healing, and morality in early heavenly master Daoism / Chi-Tim Lai -- Imagining community : family values and morality in the Lingbao scriptures / Stephen R. Bokenkamp -- What is geyi, after all? / Victor H. Mair -- The Buddharāja image of Emperor Wu of Liang / Kathy Cheng-Mei Ku -- Social and cultural dimensions of reclusion in early medieval China / Alan Berkowitz -- Destiny and retribution in early medieval China / Yuet-Keung Lo